Exploring Vehicle Cabin Noise Patterns Using an Arduino-Integrated Sound Level Meter - Ayub, Nurhan (Journal of Emerging Technologies and Industrial Applications, 2025)
Noise engendered attributable to vibrations distresses the comfort besides performance of drivers and passengers in vehicles. This study evaluates the noise levels within the cabin of a Perodua Viva Elite 1.0cc under stationary and dynamic conditions. An Arduino-based low-cost coding and a professional sound level meter were used for data collection. The findings reveal that noise levels correlate with engine RPM and vehicle speed as well as the Arduino can be used as a instrument measurement. The Arduino system demonstrated its utility as a viable alternative for dynamic noise measurement. This research emphasizes the need for enhanced cabin noise control measures to improve user comfort and safety.